HALO AND REVERSE HALO SIGNS IN CANINE PULMONARY COMPUTED TOMOGRAPHY. Issue 3 (13th January 2014) - Secrest, Scott; Sakamoto, Kaori
<x xml:space="preserve">Abstract</x> The halo sign (HS) and reverse halo sign (RHS) are radiologic signs identified on pulmonary computed tomography (CT) in people. The HS is described as a circular area of ground‐glass attenuation surrounding a pulmonary nodule or mass. The RHS is defined as a focal, rounded area of ground‐glass attenuation surrounded by a more or less complete ring of consolidation. These signs have been identified in a variety of diseases in people. The purpose of this retrospective study was to determine if the HS and RHS occur in dogs with pulmonary disease and to determine if they are associated with a particular disease process. In addition, the appearance of the HS and RHS was correlated with the histopathologic changes. Our results indicate that the HS and RHS are not common signs identified in dogs with pulmonary disease with an HS noted in five cases and an RHS in 4 of the 33 dogs that met the inclusion criteria. An association between the HS (P‐value 0.8163) or RHS (P‐value 0.5988) and neoplasia, infectious/inflammatory, and other disease processes was not identified using a Fisher's exact test. The HS was identified in neoplastic, infectious, and inflammatory conditions, with the RHS identified in neoplastic and infectious diseases and a lung lobe torsion. Histologically, the HS and RHS were caused by tumor extension, necrosis, and/or hemorrhage of the pulmonary parenchyma.